Effect Of Combination Benson Relaxation Therapy And Lavender Aromatherapy On The Decrease Blood Pressure In The Elderly With Hypertension In Working Area Of Madurejo Health Center Pangkalan Bun Province Central Borneo - qorahman, wahyudi; Syahleman, Rukmini; Fatmawati, Zuliya Indah; Setiawan, Jodi (Holistic Nursing Plus, 2024)
Background: Hypertension is a condition where blood pressure exceeds normal limits, namely systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg on repeated examinations. Hypertension, commonly known as high blood pressure, is caused by abnormalities in the blood arteries, preventing oxygen and nutrients from reaching the body's tissues. As an alternative treatment, the combination of Benson relaxation therapy and lavender aromatherapy has similarities in the mechanism of action, as seen in how the Benson relaxation technique works, namely focusing on specific words or sentences that are repeated repeatedly with a regular rhythm accompanied by an attitude of surrender to God Almighty while drawing deep breaths. While lavender aromatherapy works on both the physical and emotional levels, it can also help to lower anxiety, high blood pressure, heart rate, and stress. Lavender also stimulates the production of the hormones melatonin and serotonin. Aromatherapy can be used in a variety of methods, such as steam, inhalation, and compresses. Purpose : the aim of this study was to determine whether there is a combination effect of Benson relaxation therapy and lavender aromatherapy on reducing blood pressure in elderly hypertension at Madurejo Public Health Center in Pangkalan Bun. Methods: This type of quasi-experimental research used a one-group pre-test and post-test design with a sample of 30 respondents and purposive sampling. Blood pressure measurement using a tensimeter and an observation sheet using the Wilcoxon test. Results: The results showed that the blood pressure of hypertension sufferers pre-tested in category 1 was mild at 33.3%, moderate at 56.7%, and severe at 10.0%. The results of the level of type 2 diabetes mellitus post-test were in the good category (83.7%) and sufficient (16.3%). The Wilcoxon test results obtained a p value of 0.000. Conclusion: There is an effect of a combination of Benson relaxation therapy and lavender aromatherapy on reducing blood pressure in elderly hypertension at Madurejo Public Health Center, Pangkalan Bun, Central Kalimantan.